Pencemaran Nama Baik Melalui Sarana Informasi dan Transaksi Elektronik (Kajian Putusan MK No. 2/PUU-VII/2009) - Mahrus Ali (The Constitutional Court of the Republic of Indonesia, 2010)
Libel crime is an offence attacking the honor and image of person. There are at least two elements in the libel crime in which a judge has an obligation to prove them, subjective and objective element as well as malice. An offender cannot be blamed for his/her conduct unless he/she commits these elements. In the term of article 27 (3) of electronic transaction and information act no 11 of 2008, its content is still in accordance with the rule of law conception and several articles of Indonesia Constitution of 1945 dealing with some fundamental rights of citizen and the right of freedom to express and to obtain information. State has untitled to make any limitation by prohibiting certain activities attacking the honor and image of person which is based on the same rights of the same freedom.